2019
DOI: 10.1007/s00268-019-04945-9
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Dor or Posterior Toupet with Heller Myotomy for Achalasia Cardia: A Systematic Review and Meta‐Analysis

Abstract: Background and Aims Partial fundoplication is commonly performed in conjunction with Heller Myotomy. It is, however, controversial whether anterior Dor or posterior Toupet partial fundoplication is the antireflux procedure of choice. The aim was to perform a systematic review and meta-analysis of studies comparing these two procedures. Material and Methods A search of PubMed, Cochrane database, Medline, Embase, Science Citation Index, Google scholar and current contents for English language articles comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
(80 reference statements)
0
8
0
2
Order By: Relevance
“…For this reason, LHM coupled with an antireflux fundoplication is standardly performed. 6 Regarding choice of partial fundoplication technique, neither anterior 180-degree Dor nor posterior 270-degree Toupet fundoplication have demonstrated superiority. A recent randomized controlled trial comparing LHM with either Dor or Toupet fundoplication demonstrated no difference in function outcomes 12 months postoperatively.…”
mentioning
confidence: 99%
“…For this reason, LHM coupled with an antireflux fundoplication is standardly performed. 6 Regarding choice of partial fundoplication technique, neither anterior 180-degree Dor nor posterior 270-degree Toupet fundoplication have demonstrated superiority. A recent randomized controlled trial comparing LHM with either Dor or Toupet fundoplication demonstrated no difference in function outcomes 12 months postoperatively.…”
mentioning
confidence: 99%
“…They noted no difference between Dor and Toupet regarding acid reflux symptoms. These data were confirmed by two additional randomized controlled studies and two meta-analyses [7,8,21,22]. Considering these data, which fundoplication method to be used was left to the surgeon's preference.…”
Section: Discussionmentioning
confidence: 74%
“…In contrary, the Toupet approach is less standardized and time-consuming when looking to achieve circumferential esophageal mobilization, which may prevent scarring and adhesion of the separated muscle edge, while also reducing recurrent dysphagia. [ 42 , 43 ] Recently, two meta-analyses [ 44 , 45 ] have revealed equivalent results, while Siddaiah-Subramanya et al additionally reported that Toupet fundoplication is better than Dor in terms of length of hospitalization and quality of life. In our study, LHM + Toupet ranked higher than LHM + Dor in both short-term and mid-term efficacy, although not significantly, while only LHM without fundoplication showed worse gastroesophageal acid reflux than PD.…”
Section: Discussionmentioning
confidence: 99%